Beta-1,3/1,6-D-Glucan Extracted from Ganoderma lucidum as Adjunct Therapy in Ulcerative Colitis: A Case Series - Saskia Aziza Nursyirwan; Marcellus Simadibrata; Rabbinu Rangga Pribadi; Virly Nanda Muzelina; Hasan Maulahela; Amanda Pitarini Utari; Enrik John Aguila; Ardhia Fefrine Indarta (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2026)
The management of ulcerative colitis is primarily focused on the prevention of complications, remission sustenance, and enhancement of overall quality of life. However, long-term use of various pharmacological therapies can be associated with several side effects, including myelosuppression, hepatitis, lupus-like syndrome, and an increased risk of malignancy. These limitations have led to the search for safer therapeutic options, including bioactive compounds such as Beta-1,3/1,6-D-Glucan with immunomodulatory properties. Ganoderma lucidum contains Beta-1,3/1,6-D-Glucan as a principal bioactive compound extracted from its mycelium. Despite the broad therapeutic properties, exploration into its role specifically for ulcerative colitis patients remains scarce. Therefore, this case series aimed to explore the potential role of Beta-1,3/1,6-D-Glucan derived from Mycelium extract of Ganoderma lucidum in managing ulcerative colitis.